2023
DOI: 10.3390/horticulturae9101098
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis of Onion (Allium cepa L.) from the Arid Region of Tunisia Using Phenotypic Traits and SSR Markers

Amel Chalbi,
Hela Chikh-Rouhou,
Najla Mezghani
et al.

Abstract: The present study was carried out to evaluate and characterize, for the first time, the genetic potential of a collection of onion (Allium cepa L.) local accessions from the arid region of southern Tunisia. The genetic diversity among 135 onion individuals, belonging to 23 accessions, was evaluated using microsatellite (SSR) markers and phenotypic information. A total of 35 alleles were generated with 11 SSRs. The polymorphic information content (PIC) value ranged from 0.08 to 0.95, with an average PIC of 0.43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…While AFLP (Amplified Fragment Length Polymorphism) markers have been employed to explore genetic diversity and structure [6], challenges arise from the hexaploid nature of C. reticulata, which also includes octaploid and decaploid cultivars [7,8]. Traditional molecular markers, such as AFLP, ITS (Internal Transcribed Spacer), and SSR (Simple Sequence Repeat), may present complications, such as double bands during amplification and multi-peaks during sequencing in polyploid groups [9][10][11]. It has been reported that the phylogenetic relationships of C. reticulata cultivars, based on ITS copies from clones, are confounded by the presence of numerous ITS pseudogenes [12].…”
Section: Introductionmentioning
confidence: 99%
“…While AFLP (Amplified Fragment Length Polymorphism) markers have been employed to explore genetic diversity and structure [6], challenges arise from the hexaploid nature of C. reticulata, which also includes octaploid and decaploid cultivars [7,8]. Traditional molecular markers, such as AFLP, ITS (Internal Transcribed Spacer), and SSR (Simple Sequence Repeat), may present complications, such as double bands during amplification and multi-peaks during sequencing in polyploid groups [9][10][11]. It has been reported that the phylogenetic relationships of C. reticulata cultivars, based on ITS copies from clones, are confounded by the presence of numerous ITS pseudogenes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating phenotypic identification and molecular markers can enhance the accuracy of genetic diversity studies. This is because molecular markers solely identify variations at the DNA level, which may not necessarily manifest in observable traits (phenotypes) [32][33][34]. To select excellent hybrid combinations and obtain high-quality innovative varieties, it is necessary to identify and analyze sugar beet germplasm resources.…”
Section: Introductionmentioning
confidence: 99%